Activation of monocytes and early manifestations of cardiovascular diseases in patients with immuneinflammatory rheumatic diseases - M. V. Shalygina (Научно-практическая ревматология, 2025)
Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are immunoinflammatory rheumatic diseases (IRDs) associated with a high risk of developing cardiovascular diseases (CVD). Despite advances in diagnostics and therapy, the risk of cardiovascular pathology is 1.8–2.8 times higher than in individuals without autoimmune diseases, is increased at an early stage of the disease, and is associated with high clinical activity, disease duration, need for hospitalization, and mortality. According to modern data, CVD in patients with SLE and RA is considered a consequence of a systemic (subclinical) inflammatory process induced by pathological activation of the main components of innate and acquired immunity, more often developing in patients with low or moderate cardiovascular risk. The main cells of the innate immune system involved in the development and maintenance of inflammation are monocytes and macrophages. There are two main phenotypes of macrophages: M1 (proinflammatory) and M2 (anti-inflammatory). M1 macrophages produce the main proinflammatory cytokines interleukin (IL) 6, IL-23, tumor necrosis factor α, which are involved in maintaining inflammation by engaging new immune cells, while M2 secrete anti-inflammatory mediators and limit inflammation. It is assumed that an imbalance between the two phenotypes may underlie SLE, RA, and the development of early manifestations of CVD.Currently, various diagnostic non-invasive methods are used to visualize subclinical CVD, the results of which can provide additional values for risk stratification for asymptomatic patients. The importance of monitoring arterial stiffness as one of the markers characterizing vascular remodeling in the development of early signs of atherosclerosis has been confirmed. Several studies have demonstrated the effectiveness of new echocardiographic techniques (tissue Doppler), especially global longitudinal strain using speckle tracking, in assessing subclinical cardiac damage and left ventricular diastolic dysfunction. Thus, clarifying the relationship between proinflammatory monocyte activation and early cardiovascular disorders in patients with SLE and RA will contribute to understanding the common pathogenetic mechanisms in IRDs and CVD.